Rape: The Role of Histocytopathologist in Nigeria - Victor Ekundina; Chiamaka Ejelue; Emmanuel Omon (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aim. Sexual violence refers to a specific constellation of crimes including sexual harassment, sexual assault, and rape. This study was carried out to establish the role of histocytopathologist in establishing rape cases in Nigeria. Methods. One of the first interventions is the macroscopic analysis that consists of evaluating evidence/garments collected (from the victim, corpse, aggressor, and crime scene) to the laboratory in order to perform a search for blood, semen, hair, saliva, sweat, tissues, fibers, and other elements through meticulous and sequential observation, evaluating and establishing strategies to find biological spots. Coloscopic analysis was done using the histological stain; Toluidine blue. Results. Identification by microscopy (e.g., spermatozoa), comparison microscopy (e.g., hairs and fibers), serological analyses (e.g. conventional ABO grouping or species identification), and biochemical analyses (e.g. phosphoglucomutase) played a fundamental role in the investigation of crime for many years and are still used today in some circumstances. In the forensic analysis of male on male rape, microscopic examination for spermatozoa is initially undertaken, followed by DNA analysis if any body fluids are identified. Conclusion. The role of a histocytopathologist in rape diagnosis include detection of biological evidence using microscopic techniques, assessment of a crime scene using Alternative Light Sources, use of fluorescent contrast techniques and use of histochemistry and staining methods to detect and analyze biological evidence.